Analisa Penentu Flipping Activity pada Saham-Saham IPO di Indonesia - Cynthia Sari Dewi; Helena Dewi (PT FORMOSA CENDEKIA GLOBAL, 2022)
By conducting an Initial Public Offering (IPO), investors have the opportunity to do flipping activities. Although this activity indicates secondary market liquidity, heavy flipping is not favored by underwriters because it is considered detrimental to the performance of IPO shares. This study aims to analyze the factors that can encourage investors to carry out flipping activities at the time of the IPO. This study uses IPO shares in 2019, where there are 40 of 54 IPO shares. This research is a multiple regression which is then processed using IBM SPSS version 24 software. The results show that the variables that significantly affect flipping activity are initial return and oversubscription ratio. Meanwhile, firm age and firm size do not significantly affect flipping activity. The results of the study can be used as a reference for investors and issuers regarding the performance of IPO shares